2016
DOI: 10.1142/s021798491650086x
|View full text |Cite
|
Sign up to set email alerts
|

Topological supersymmetry breaking: The definition and stochastic generalization of chaos and the limit of applicability of statistics

Abstract: The concept of deterministic dynamical chaos has a long history and is well established by now.Nevertheless, its field theoretic essence and its stochastic generalization have been revealed only very recently. Within the newly found supersymmetric theory of stochastics (STS), all stochastic differential equations (SDEs) possess topological or de Rahm supersymmetry and stochastic chaos is the phenomenon of its spontaneous breakdown. Even though the STS is free of approximations and thus is technically solid, it… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 42 publications
(97 reference statements)
0
19
0
Order By: Relevance
“…Therefore, when TS is broken spontaneously, Γ g together with S are positive, and it immediately follows that the phenomenon of the spontaneous breakdown of TS must be associated with the stochastic generalization of dynamical chaos [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when TS is broken spontaneously, Γ g together with S are positive, and it immediately follows that the phenomenon of the spontaneous breakdown of TS must be associated with the stochastic generalization of dynamical chaos [42].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, TS is the preservation of the proximity of points in phase space during evolution. This interpretation makes it particularly clear that the spontaneous breakdown of TS must be viewed as the stochastic generalization of dynamical chaos [42,43]. Indeed, the spontaneous breakdown of TS must imply that initially close points may not be close anymore after an infinitely long evolution, when the system is described by a non-supersymmetric ground state.…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that such situation can be looked upon as the stochastic generalization of the concept of deterministic chaos. [9] …”
Section: Spontaneous Breakdown Of Supersymmetrymentioning
confidence: 99%
“…[8] This theory is an approximation-free and coordinate-free theory of SDEs that can be dubbed the supersymmetric theory of stochastics (STS) and that has provided a rigorous stochastic generalization of the concept of deterministic dynamical chaos. [9] Another important result from the STS, [10] which is directly relevant to this paper, is revealing the theoretical essence of the stochastic dynamical behavior known as noise-induced chaos, [11] self-organized criticality, [7] intermittency [12,13] etc. and that we call for brevity the N-phase.…”
Section: Introductionmentioning
confidence: 98%
“…The approach of supersymmetric theory of stochastics (STS) focuses on the theoretical analysis of the DS as a supersymmetric system [ 18 , 19 , 20 , 21 ]. One of the central messages of stochastics (STS) is the correspondence between the spontaneous breakdown of this supersymmetry (SUSY) and the emergence of chaotic dynamics.…”
Section: Introductionmentioning
confidence: 99%